Enhancing resin-dentin bond durability using a novel mussel-inspired monomer. (September 2021) - Li, Kang; Yao, Chenmin; Sun, Yuhong; Wang, Kun; Wang, Xiangtao; Wang, Zhengzhi; Tsoi, James Kit Hon; Huang, Cui; Yiu, Cynthia Kar Yung
Abstract: Numerous approaches have been developed to improve the resin-dentin bond performance, among which the bio-application of mussel-derived compounds have drawn great attention recently. To assess the performance of N -(3, 4-dihydroxyphenethyl)methacrylamide (DMA), a mussel-derived compound, as a functional monomer in dental adhesive, its potential property to cross-link with dentin collagen and polymerize with adhesive will first be evaluated by transmission electron microscopy (TEM), attenuated total reflectance technique of Fourier transform infrared (ATR-FTIR), and atomic force microscopy (AFM) via Peakforce QNM mode. After validating the influence of DMA on collagen and adhesive separately, the overall performance of DMA/ethanol solution as a primer in dentin bonding was examined using micro-tensile bond strength (μTBS) testing, fracture pattern observation, and nanoleakage evaluation both immediately and after 10, 000 times thermocycling aging. The inhibitory effect of DMA on endogenous metalloproteinases (MMPs) was evaluated by in situ zymography using confocal laser scanning microscopy (CLSM) and the cytotoxicity of DMA was evaluated using cell counting kit-8. Results demonstrated that DMA successfully cross-linked with dentin collagen via non-covalent bonds and had no influence on the polymerization and mechanical properties of the adhesive. Furthermore, even after 10, 000 times thermocycling aging, the μTBS and nanoleakage expression of the DMA-treated groups showed no significant change compared with their immediate values. In situ zymography revealed reduced endogenous proteolytic activities after the application of DMA, and no cytotoxicity effect was observed for DMA concentration up to 25 ​μmol/L. Thus, DMA could be used as a novel, biocompatible functional monomer in dentin bonding. Graphical abstract: Image 1 Highlights: DMA acts as a functional monomer in dentin bonding system with high biocompatibility. DMA connects the adhesive and collagen network to resist various external attacks. DMA/ethanol inhibits the activity of MMPs and improve resin-dentin bond durability.